128k views
1 vote
Simplify the expression

Simplify the expression-example-1

1 Answer

4 votes

Answer:

Option B:
2x^2 +9x - 2/ 8x^3 +4x^2 -2x -1

Explanation:

Given that:


=(3/4x^2 + 4x +1) + (x+1/ 4x^2 - 1)

By simplifying and factorizing we get:


= (3/ 4x^2 + 2x + 2x +1) + (x+1/ (2x^2)-(1)^2)\\= (3/ 2x(2x+1)+1(2x + 1)) + (x+1/(2x+1)(2x - 1))\\= (3/(2x + 1)^2) + (x+1/ (2x+1)(2x -1))

By taking LCM we get:


=(3(2x-1)+ (x+1)(2x + 1))/((2x+ 1)^2 (2x-1))\\= 6x -3 + 2x^2 + x + 2x +1/ 8x^3 +4x^2 -2x -1\\= 2x^2 +9x -2/8x^3 +4x -2x -1

I hope it will help you!

User Timo Geusch
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.